Acceptance of a smartphone navigation application by hospital patients and visitors: the role of gender, age, and education - Ženka, Jan; Macháček, Jan; Krtička, Luděk; Michna, Pavel; Kořízek, Pavel (Hungarian Geographical Bulletin, 2021)
This paper analyses the acceptance of a smartphone navigation app in a hospital among its patients/visitors. We tested the effects of socio-demographic factors (gender, age, and education) on technology acceptance and on perceived difficulties with wayfinding in the hospital complex. The empirical research is based on a survey among 928 patients/visitors of the Vítkovice Hospital in Ostrava, Czechia. We found that the acceptance of smart navigation increases with the level of education and decreases with age. No significant gender differences were observed.